The Influence of Organizational Culture on Affective and Normative Commitment to Employees in The Construction Sector in Bandung - Yani Cendrayani; Iwan Sidharta (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2020)
The research carried with the phenomenon of not optimal construction implementation indicates a lack of work commitment of construction sector employees. From the problem of work commitment, this study aims to determine the effect of organizational culture on affective commitment and normative commitment to employees in the construction sector in Bandung. The research method used is quantitative research methods with regression analysis techniques. Respondents who use as a sample were 139 employees from 301 Construction Business Entities in Bandung City. The results showed that organizational culture has a significant effect on affective commitment and normative commitment of construction employees. The results indicated that a healthy organizational culture would increase the affective and normative commitment of construction employees. Efforts that must improve the organizational culture on employee commitment, it is hoped that the service company will further enhance the organizational culture, especially for the aspect. There is harmonious cooperation among employees.